Use of graphene oxide for the removal of norfloxacin and ceftriaxone antibiotics from aqueous solution: process optimization using response surface approach - Li, Zhihui; Zhang, Shuhang; Zhu, Guina; Xing, Jie (Frontiers in Environmental Science, 2024)
In this research, graphene oxide (GO) as an adsorbent was used to remove norfloxacin and ceftriaxone antibiotics from aqueous solutions. All environmental factors affecting removal (e.g., pH, adsorbent mass, contact time, and concentration) were optimized in a discontinuous system. The design of experiments and the optimization of variables were carried out using the response surface method (RSM). The results of the analysis of variance (ANOVA) and the regression coefficients of the quadratic terms indicated that the responses were significantly affected by all the studied variables (P < 0.05). Also, the quadratic polynomial model results corresponded to empirical data with a high coefficient of determination (i.e., R 2 ˃ 0.99 for both antibiotics). Besides, the adjusted R 2 (R 2 -adj ˃ 0.98 for both antibiotics) was close to R 2 values, indicating a good and acceptable statistical model. According to the results, the optimal removal of antibiotics by GO occurs in conditions of pH of 8, 0.034 g of the adsorbent mass, a sonication time of 20 min, and a concentration of 25 mg L -1 . In these conditions, the maximum removal efficiencies of ceftriaxone and norfloxacin were equal to 95.87% and 98.64%, respectively. GO was recovered in five adsorption/desorption processes, and the removal efficiency declined very slightly after using the adsorbent for five cycles. Therefore, it is concluded that GO is an efficient and acceptable adsorbent for removing ceftriaxone and norfloxacin from aqueous environments.